Development of the spectrum transmittance measurement system for large-size optical elements of Cherenkov telescope. (1st July 2022) - Geng, Lisi; Hor, Y.K.; Min, Zhen; Wang, Yudong; Yang, Mingjie; Yang, Jiaying; Zhang, Shoushan; Zhang, Yong
Abstract: The Cherenkov and fluorescence telescopes are used to detect cosmic rays in many large-scale experiments. Certain large-size optical elements, such as quartz glasses with window and filters, are installed in front of cameras as the window to seal the cameras and minimize the impact of the night sky background light. The transmittance of those optical elements in Cherenkov and fluorescence telescopes is therefore vital for the measurement of the number of photons reaching the camera. The uniformity is an important parameter of transmittance at different wavelength over the whole window surface. It is difficult to ensure the uniformity of the window material when it is produced, especially for the size as large as 1 m 2 . The measurement of the uniformity of the transmittance of filters at different positions on the window, and over a large optical spectrum, is not a trivial task and therefore a dedicated system has been developed. The large-size filter transmittance measurement system can measure the spectrum range from 250 nm to 900 nm. A two dimensional motorized device is used to carry the system and the accuracy of the system is up to 0.01 mm. In addition, the measuring system can measure the transmittance at an incident angle ranging from 0° to 44°. The relative standard deviation can be reduced to less than 1% by alternately measuring with and without samples. The transmittance spectra of the neodymium glass standard sheets and quartz glass JGS2, of size 876 mm × 862 mm × 4 mm have been measured with this system and compared. The result of neodymium glass indicates that the system can measure the transmittance spectrum precisely, up to 1% uncertainty. The results of the JGS2 quartz glass demonstrate that our system is capable of measuring the optical parameters of very large sample with a precision at the level of 1% over a wide spectrum range.